Management of Religious Learning Curriculum at Al-Ma'soem Boarding School Bandung - Indah Wahyu Ningsih; Annisa Mayasari; Bambang Samsul Arifin (Universitas Muhammadiyah Enrekang, 2022)
This study aims to explain the management of the religious learning curriculum at Al-Ma'soem boarding school. This study uses a descriptive method with a qualitative approach. The results of this study indicate that boarding schools or boarding schools combine the Islamic boarding school education system and the national education system. The integration of these two education systems gave birth to a more synergistic and independent form of education. There is a model of integration of Islamic boarding school education with school education which is the forerunner of boarding schools or boarding schools. boarding school places more emphasis on morality and upholds the values ​​of independence, simplicity and the like. Al-Ma'soem boarding school aims to create a perfect human being (Insan Kamil) which later becomes the motto in Sundanese